Association of triglyceride-glucose index (TyG) and a body shape index (ABSI) with cognitive decline and dementia risk - Shuangshuang Yang; Lili Cui; Jinxin Zhang; Ying Yang; Junhao Huo; Yuyan Ding; Jingni Zhang; Shulan He; Jiangping Li (PLoS ONE, 2026)
Background Longitudinal evidence linking the body shape index (ABSI) to dementia and its subtypes remains scarce. Furthermore, the use of ABSI and TyG-ABSI as predictors of cognitive decline and dementia is infrequent. Therefore, this study aimed to examine the relationships between the triglyceride-glucose (TyG) index, ABSI, and TyG-ABSI indices and their predictive value for cognitive decline and dementia risk. Methods This study included 370,744 participants from the UK Biobank. The TyG and ABSI indices were calculated using their respective formulas, while the TyG-ABSI index was derived by multiplying TyG and ABSI. Cognitive decline was defined as scoring in the bottom 25% on cognitive tests, while dementia was diagnosed from first-recorded incidents and algorithmically-defined outcomes. Logistic regressions were employed to assess the associations of TyG, ABSI and TyG-ABSI indices with cognitive decline; Cox regressions were used to analyze the associations of these indices with the risk of all-cause dementia (ACD) and its subtypes. Result The TyG, ABSI, and TyG-ABSI indices were all significantly associated with cognitive decline. Additionally, compared with the lowest quartiles, the highest quartiles of TyG, ABSI and TyG-ABSI indices were associated with a significantly increased risk of ACD by 33% (HR = 1.33, 95% CI: 1.13–1.57), 79% (HR = 1.79, 95% CI: 1.65–1.94) and 67% (HR = 1.67, 95% CI: 1.54–1.82), respectively. These indices were also significantly associated with the risk of Alzheimer’s disease (AD) and vascular dementia (VD) (all P < 0.05). Conclusion The TyG, ABSI, and TyG-ABSI indices are significantly and positively linked to the risk of cognitive decline and dementia.